2021
DOI: 10.1371/journal.pone.0245068
|View full text |Cite
|
Sign up to set email alerts
|

Development of a modular stress management platform (Performance Edge VR) and a pilot efficacy trial of a bio-feedback enhanced training module for controlled breathing

Abstract: This paper describes the conceptual design of a virtual reality-based stress management training tool and evaluation of the initial prototype in a pilot efficacy study. Performance Edge virtual-reality (VR) was co-developed with the Australian Defence Force (ADF) to address the need for practical stress management training for ADF personnel. The VR application is biofeedback-enabled and contains key stress management techniques derived from acceptance and commitment and cognitive behavioural therapy in a modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 56 publications
1
29
0
2
Order By: Relevance
“…Of the 32 studies, 24 involved healthy individuals [ 6 , 8 , 10 , 24 , 26 , 28 - 38 , 40 , 41 , 43 - 48 ], 1 involved individuals at high risk of developing anxiety disorders [ 39 ], 1 involved patients with lung cancer [ 7 ], 1 involved patients with pneumonia [ 49 ], 2 involved patients with COPD [ 27 , 42 ], 2 involved patients with COVID-19 [ 49 , 50 ], and 1 involved patients with asthma [ 5 ]. The breathing exercises were mostly related to breathing therapy (9/32) [ 5 , 6 , 10 , 25 , 27 , 33 , 48 , 49 , 54 ] and anxiety management (13/32) [ 8 , 28 , 29 , 32 , 34 , 36 , 37 , 39 - 41 , 43 - 45 ]. Most of the reviewed papers based their research on pilot (16/32) or control studies (11/32), while some of the papers (4/32) only described the design and development processes of their systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 32 studies, 24 involved healthy individuals [ 6 , 8 , 10 , 24 , 26 , 28 - 38 , 40 , 41 , 43 - 48 ], 1 involved individuals at high risk of developing anxiety disorders [ 39 ], 1 involved patients with lung cancer [ 7 ], 1 involved patients with pneumonia [ 49 ], 2 involved patients with COPD [ 27 , 42 ], 2 involved patients with COVID-19 [ 49 , 50 ], and 1 involved patients with asthma [ 5 ]. The breathing exercises were mostly related to breathing therapy (9/32) [ 5 , 6 , 10 , 25 , 27 , 33 , 48 , 49 , 54 ] and anxiety management (13/32) [ 8 , 28 , 29 , 32 , 34 , 36 , 37 , 39 - 41 , 43 - 45 ]. Most of the reviewed papers based their research on pilot (16/32) or control studies (11/32), while some of the papers (4/32) only described the design and development processes of their systems.…”
Section: Resultsmentioning
confidence: 99%
“…All the reviewed studies (32/32) collected participants’ demographic information (eg, age, sex, ethnicity, educational level, etc). Half of the reviewed studies (14/32) examined the effect of VR breathing training on mental health (ie, anxiety) [ 6 , 25 , 26 , 28 - 30 , 32 , 34 , 36 , 37 , 39 - 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that XR technology has limitations and may be suited for some teaching and learning objectives more than others. Evidence highlights that XR teaching tools can effectively improve practical skills development (Bouaicha et al, 2020;Canto et al, 2013;Falah et al, 2015;Garfjeld Roberts et al, 2017;Kluge et al, 2021;Legault et al, 2019;Nicholson et al, 2006;Vieira et al, 2017). An XR tool addressing practical skills has the most value when otherwise ethically inappropriate, expensive, and/ or logistically impossible to provide.…”
Section: Focus On Learning Objectives and Priority Areasmentioning
confidence: 99%
“…In these areas procedural training using XR is particularly beneficial for the development of practical skills (Bouaicha et al, 2020;Canto et al, 2013;Falah et al, 2015;Garfjeld Roberts et al, 2017;Kluge et al, 2021;Legault et al, 2019;Nicholson et al, 2006;Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the easiest methods for managing stress-related symptoms is deep breathing exercises [ 3 ]; these exercises have been proposed as first-line and supplemental treatments for emotional disorders [ 35 ]. Several studies reported that the use of different breathing techniques showed significant improvement in mood states and perceived stress [ 36 , 37 ] resulting in an effective improvement in the management of stress in daily life [ 36 ]. Slow and deep breathing can have a significant impact on reducing stress feelings and activating the relaxation response.…”
Section: Introductionmentioning
confidence: 99%